A randomized controlled trial to evaluate the efficacy of metacognitive training for older adults with depression (MCT-Silver) in Portugal: study protocol - Pinho, Lara Guedes de; Silva, Celso; Fonseca, César; Morgado, Bruno; Lopes, Manuel; Moritz, Steffen; Jelinek, Lena; Schneider, Brooke C. (Frontiers in Psychology, 2023)
Introduction:. Depression is one of the most common psychological disorders in later lifve. Although psychological interventions are recommended by treatment guidelines, most older adults with depression remain untreated. The aim of this study is to evaluate the efficacy of the Portuguese version of Metacognitive Training for Depression in later life (MCT-Silver).Methods: This is a study protocol of an observer-blind, parallel-group, randomized controlled trial to compare the efficacy of MCT-Silver with a a treatment as usual (TAU) control group among older adults (age 65 years and older) with depressive symptoms according to the Montgomery-Asberg Depression Scale. Participants will be tested at three assessment time points (baseline, immediately following the intervention [8 weeks], and 3 months after the intervention). The primary outcome is change in self-rated depression symptoms assessed by the Beck's Depression Inventory (BDI-II). Secondary outcomes include clinician-rated depression, self-esteem, dysfunctional beliefs, metacognitive beliefs, ruminations, attitudes toward aging and quality of life. A self-designed subjective appraisal rating scale consisting of 21-items will be used to assess participant acceptance of MCT-Silver. This is a provisional file, not the final typeset article Discussion: MCT-Silver is an innovative intervention, which aims to reduce dysfunctional thoughts as well as depression-related behaviours and coping strategies through the metacognitive perspective. Until now, the training has only been tested in Germany. It is expected that after eight weeks of treatment and three months later, the experimental group will demonstrate significant reductions in depressive symptoms, metacognitive beliefs, dysfunctional attitudes and ruminative responses compared to the TAU group. Moreover, quality of life, self-esteem, and attitudes towards ageing will be significantly improved in MCT-Silver compared to the TAU group.The trial has been registered at ClinicalTrials.gov (NCT05640492).